Measuring future liver remnant function prior to hepatectomy may guide the indication for portal vein occlusion and avoid posthepatectomy liver failure: a prospective interventional study. Issue 2 (February 2017) - Chapelle, Thiery; Op de Beeck, Bart; Roeyen, Geert; Bracke, Bart; Hartman, Vera; De Greef, Kathleen; Huyghe, Ivan; Van der Zijden, Thijs; Morrison, Stuart; Francque, Sven; Ysebaert, Dirk
Abstract: Background: Estimation of the future liver remnant function (eFLRF) can avoid post-hepatectomy liver failure (PHLF). In a previous study, a cutoff value of 2.3%/min/m 2 for eFLRF was a better predictor of PHLF than future liver remnant volume (FLRV%). In this prospective interventional study, investigating a management strategy aimed at avoiding PHLF, this cutoff value was the sole criterion assessing eligibility for hepatectomy, with or without portal vein occlusion (PVO). Methods: In 100 consecutive patients, eFLRF was determined using the formula: eFLRF = FLRV% × total liver function (TLF). Group 1 (eFLRF >2.3%/min/m 2 ) underwent hepatectomy without preoperative intervention. Group 2 (eFLRF <2.3%/min/m 2 ) underwent PVO and re-evaluation of eFLRF at 4–6 weeks. Hepatectomy was performed if eFLRF had increased to >2.3%/min/m 2, but was considered contraindicated if the value remained lower. Results: In group 1 (n = 93), 1 patient developed grade B PHLF. In group 2 (n = 7) no PHLF was recorded. Postoperative recovery of TLF in patients with preoperative eFLRF <2.3%/min/m 2 occurred more rapidly when PVO had been performed. Conclusion: A predefined cutoff for preoperatively calculated eFLRF can be used as a tool for selecting patients prior to hepatectomy, with or without PVO, thus avoiding PHLF and PHLF-related mortality.